Evaluating health promotion : practice and methods - Thorogood, Margaret; Coombes, Yolande (Oxford ; New York : Oxford University Press, 2010)
"Health Promotion is a relatively new discipline and there is little in the way of practical help for students and practitioners in choosin g and implementing appropriate evaluation methods. As the demands for r igorous evaluation and evidence-based decision-making increase, health promotion cannot ignore the need for accurate, reliable and valid metho ds to carry out evaluation. This book provides clear descriptions (with plentiful practical examples) of such methods, and the problems that c an arise from their implementation. Both qualitative and quantitative m ethods that are commonly used are described and the problems and benefi ts that arise with their use are explained. Experiences in the practica l implementation of evaluation are explained, with examples from a vari ety of different social, economic and cultural contexts. The third edit ion of this highly successful book has been fully revised and updated t o reflect the ongoing developments in the field of health promotion. It will appeal to students and practitioners in health promotion and publ ic health (including programme managers in both the government and the voluntary sector), and donors and funding agencies who commission healt h promotion interventions and evaluations"--Provided by publisher.
Machine generated contents note: -- 1: Overview 1. Introduction, Yolande Coombes and Margaret Thorogood2. Histori cal and policy approaches, Virginia BerridgePart 2: Me thods of evaluation 3. Evaluating according to purpose and res ources: Strengthening the evidence base incrementally, Yolande Coom bes4. Evaluating interventions: Experimental study designs in heal th promotion, Annie Britton5. Economic evaluation of health pr omotion interventions, Warren Stevens6. Using systematic revie ws in health promotion, Margaret Thorogood7. Process evaluatio n: Understanding how and why interventions work, David Ellard and S uzanne ParsonsPart 3: Evaluation in practice 8. S ocial marketing interventions and evaluation, Steven Chapman9. Evaluation of interventions to prevent intimate partner violence, Rachel Jewkes10. Evaluating environmental interventions through na tural experiments, Melvyn Hillsdon11. E-health promotion, John PowellPart 4: Participants in, and users of, evaluati on 12. Involving lay people in the development of NICE public health guidance, Jane Cowl13. Evaluating the ethics of health promotion: Understanding informed participation, Dalya Marks14 . Feeding back evaluation results to stakeholder participants, Yola nde Coombes15. Getting findings into policy, Carol Tannahill</ em>16. Conclusions: Providing appropriate evidence and influencing poli cy, Margaret Thorogood and Yolande Coombes.
Includes bibliographical references and index.
Keywords: Health promotion -- Evaluation; Health Promotion -- standards; Outcome and Process Assessment (Health Care) -- methods; Program Evaluation -- methods